PEMBUATAN PENDETEKSI OBYEK DENGAN METODE YOU ONLY LOOK ONCE (YOLO) UNTUK AUTOMATED TELLER MACHINE (ATM) - Wasril, Abi Rachman; Ghozali, Mohammad Shiddiq; Mustafa, M Banu (Majalah Ilmiah UNIKOM, 2019)
The development of Information and Communication Technology is so rapid in this day and age. Also followed by developments in the field of Artificial Intelligence (AI). In Indonesia itself is still not very popular among the public, but IT companies are competing to create innovations in the field of Artificial Intelligence and the application of Artificial Intelligence in all aspects of life. For example in Automated Teller Machines (ATM), there are often ATM crimes such as pin number surveillance, skimming, Lebanese loops and other crimes. Even though there are CCTVs in ATMs, criminals use tools to cover their faces such as helmets, hats, masks and sunglasses. Usually in front of the ATM entrance there is a prohibition against using helmets, hats, masks and sunglasses and not carrying cigarettes. However, the ban still violates, because there is no follow-up when someone uses objects that are prohibited from being brought into the ATM. Therefore an object detection system is applied in the field of Artificial Intelligence to detect objects that are prohibited from being used when at an ATM. One method used to create Object Detection is You Only Look Once (YOLO). Implementation of this idea is available on DARKNET (open source neural network). The way YOLO works is by looking at the whole picture once, then passing through the neural network once it directly detects the existing object. Therefore, it is called You Only Look Once (YOLO). Key words: Automated Teller Machine (ATM), Artificial Intelligence, Object Detection, You Only Look Once (YOLO)